The Current Trends in Livestock Product Processing: Problems and Prospects - Glushkov Oleg A. (Problemi Ekonomiki)
The strategic role of livestock product processing in ensuring food security, enhancing the competitiveness of the agro-industrial complex, and forming added value in agricultural production defines the relevance of the research. Along with this, the sector faces a number of challenges that necessitate a comprehensive study of the current state of the livestock processing industry. The relevance of the topic and the presence of previously unresolved aspects of the general problem determine the aim of the research, which is to analyze the current state and development trends of livestock product processing in Ukraine, considering external and internal challenges. To achieve the set aim, a combination of methods was applied, ensuring the systematic and substantiated nature of the research into the development of the processing industry in animal husbandry, specifically: the method of statistical analysis for assessing the dynamics of raw material supplies and indicators of added value; the method of comparisons for analyzing changes in the industry and international experience; the graphical method for visualizing trends and results obtained; systematic analysis to determine the role of the sector in forming value-added chains and ensuring food security; the method of economic-mathematical modeling for calculating indicators for individual types of products. The comprehensive use of the methods enabled a thorough analysis of the modern processes of livestock product processing. A statistical analysis of the volumes of incoming livestock raw materials to processing enterprises was conducted. The strengthening of the role of industrial enterprises as the main suppliers of raw materials for processing is substantiated, driven by high productivity and a stable procurement policy. Statistical indicators are presented that demonstrate the transformation of the structure of suppliers of milk and meat: a decrease in the share of private household farms and an increase in procurement volumes in the industrial sector. A significant increase in the processing volumes of poultry products has been identified as confirmation of the economic viability and high efficiency of this direction. The study of milk deliveries to processing enterprises has revealed crisis phenomena in the dairy industry, particularly a reduction in the overall volume of milk production in Ukraine and a decrease in the share of milk from the population, caused by low farm efficiency and a lack of incentives for modernization. The analysis of the development of the dairy processing sector has demonstrated a reduction in the number of enterprises, which is linked to a prolonged decline in production, a decrease in domestic demand, and the negative impact of the full-scale war. The volumes of production of the main types of dairy products have been analyzed, among which a sharp decline in the output of raw milk, butter, cheese, and condensed milk has been recorded, whereas the production of dry milk shows stability, indicating its potential in external markets.